2020
DOI: 10.1016/j.annonc.2020.06.006
|View full text |Cite
|
Sign up to set email alerts
|

HSD3B1 (1245A>C) germline variant and clinical outcomes in metastatic castration-resistant prostate cancer patients treated with abiraterone and enzalutamide: results from two prospective studies

Abstract: Background: A common polymorphism (1245A>C) in the HSD3B1 gene is associated with increased de novo synthesis of androgens and worse outcomes in men treated with androgen-deprivation therapy for metastatic castrationsensitive prostate cancer. The objective of the study was to determine whether this polymorphism is associated with outcomes for metastatic castration-resistant prostate cancer (mCRPC) treated with abiraterone or enzalutamide. Patients and methods: A total of 547 patients treated with abiraterone o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…In addition, HSD3B1 genetic amplification was observed in some cases with metastatic tumour and CRPC, which lead to increased 3β-hydroxysteroid dehydrogenase resulting in castration resistance by both wild type and variant type (Chang et al, 2013). Thus, for the first time, this study suggested that dehydrogenase might be implicated in anticancer efficacy by abiraterone treatment (Almassi et al, 2018;Alyamani et al, 2018;Khalaf et al, 2020;Li et al, 2015;Lu et al, 2020;Shiota, Narita, et al, 2019). Therefore, testing for somatic alteration in addition to germline genotyping in HSD3B1 would be important for precision medicine.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In addition, HSD3B1 genetic amplification was observed in some cases with metastatic tumour and CRPC, which lead to increased 3β-hydroxysteroid dehydrogenase resulting in castration resistance by both wild type and variant type (Chang et al, 2013). Thus, for the first time, this study suggested that dehydrogenase might be implicated in anticancer efficacy by abiraterone treatment (Almassi et al, 2018;Alyamani et al, 2018;Khalaf et al, 2020;Li et al, 2015;Lu et al, 2020;Shiota, Narita, et al, 2019). Therefore, testing for somatic alteration in addition to germline genotyping in HSD3B1 would be important for precision medicine.…”
Section: Discussionmentioning
confidence: 82%
“…Meanwhile, as distinct mechanism of 3β‐hydroxysteroid dehydrogenase overexpression, loss of heterozygosity by deletion of wild‐type HSD3B1 has been found in cases with heterozygous inheritance, which was shown to result in abundant expression of variant‐type 3β‐hydroxysteroid dehydrogenase (Chang et al, 2013). In addition, enzymatic activity of 3β‐hydroxysteroid dehydrogenase might be implicated in anticancer efficacy by abiraterone treatment (Almassi et al, 2018; Alyamani et al, 2018; Khalaf et al, 2020; Li et al, 2015; Lu et al, 2020; Shiota, Narita, et al, 2019). Therefore, testing for somatic alteration in addition to germline genotyping in HSD3B1 would be important for precision medicine.…”
Section: Discussionmentioning
confidence: 99%
“…The adrenal permissive variant of HSD3B1 (promotes conversion of AED and T to downstream androgens, and of abiraterone to D4 abiraterone and 3-keto-5α-abiraterone) has been consistently associated with more rapid progression on ADT (39), and potentially with worse outcomes in response to AA and enzalutamide in some but not all studies (40)(41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with higher plasma levels of progesterone after abiraterone treatment might have more potent activity of 3βHSD1, which has been reported as a risk factor of treatment failure. 69 , 70 However, the patients enrolled in this real-world analysis were not as rigorously examined as patients enrolled in clinical trials, and the patient number should be increased to confirm the role of progesterone as a predictive biomarker for the response to abiraterone.…”
Section: Discussionmentioning
confidence: 99%